2020
DOI: 10.1111/joor.13088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clear aligner therapy on tooth pain and masticatory muscle soreness

Abstract: Background: Clinical findings suggest that orthodontic treatment with clear aligners (clear aligner therapy/CAT) may cause masticatory muscle soreness in some patients. Objective: This multi-site prospective study investigated tooth pain and masticatory muscle soreness and tenderness in patients undergoing CAT and explored whether psychological traits affected these outcomes. Methods: Twenty-seven adults (22F, 5M; mean age ± SD=35.3 ± 17.6 years) about to start CAT were recruited at three clinics. During CAT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…In agreement with past research, the wearing of PCAs was sufficient to cause OD, with both groups experiencing an increase in OD after insertion of the PCAs on Aligner Day 1 40 . By Aligner Day 8, reductions in OD were recorded in all participants, indicating that some form of habituation to the aligners was taking place over time 3,40 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with past research, the wearing of PCAs was sufficient to cause OD, with both groups experiencing an increase in OD after insertion of the PCAs on Aligner Day 1 40 . By Aligner Day 8, reductions in OD were recorded in all participants, indicating that some form of habituation to the aligners was taking place over time 3,40 …”
Section: Discussionsupporting
confidence: 90%
“…No significant change in reported TMD symptoms occurred in either group in response to the PCAs. Transient increases in muscle tenderness without progression to TMD development have been reported in response to CAT 40 . Although masticatory muscle pain was not objectively assessed in our study, the lack of change in TMD symptom scores over time indicates the PCAs did not influence TMD development in the short‐term.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…57 A recent study also found that clear aligners use may cause temporary jaw pain, but no patient developed TMD and the effect was transient. 58…”
Section: Pain and Muscle Tenderness Scoresmentioning
confidence: 99%